2012
DOI: 10.1038/aps.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid inhibits autophagic flux and induces apoptosis in human multiple myeloma cells in vitro

Abstract: Aim: To investigate the effects of betulinic acid (BA) on apoptosis and autophagic flux in multiple myeloma cells and the relationship between the two processes. Methods: The proliferation of human multiple myeloma KM3 cells was measured with MTT assay. FITC/PI double-labeled flow cytometry (FCM) and Hoechst 33258 staining were used to analyze the cell apoptosis. Caspase 3, PARP, Beclin1, LC3-II, and P62 were detected using Western blotting. Results: Treatment of KM3 cells with BA (5−25 μg/mL) suppressed the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
4
25
2
Order By: Relevance
“…Furthermore, BA combined with rapamycin, an autophagic inducer, causes the synergic accumulation of p62 and LC3‐II and induction of apoptosis. Collectively, BA may have a different effect in the process of autophagy in different cancer cell lines …”
Section: Antitumor Activity Of Betulinic Acid and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, BA combined with rapamycin, an autophagic inducer, causes the synergic accumulation of p62 and LC3‐II and induction of apoptosis. Collectively, BA may have a different effect in the process of autophagy in different cancer cell lines …”
Section: Antitumor Activity Of Betulinic Acid and Its Derivativesmentioning
confidence: 99%
“…Collectively, BA may have a different effect in the process of autophagy in different cancer cell lines. 136 B10, a glycosylated derivative of BA, not only induces apoptosis, but also induces autophagy. B10 destabilizes lysosomes and releases lysosomal hydrolases, cathepsin B and Z, to the cytoplasm and induces cell death.…”
Section: Immunoregulationmentioning
confidence: 99%
“… 17 , 22 Previously, BetA and a derivative of BetA, B10, have been shown to induce autophagosome formation in multiple myeloma cells and glioblastoma cells. 23 , 24 In these studies it was suggested that the autophagic flux was prevented, leading to an accumulation of undigested autophagosomes. Although both studies observed autophagy, the role of autophagy as a cell death mechanism was not addressed for BetA.…”
mentioning
confidence: 99%
“…Although both studies observed autophagy, the role of autophagy as a cell death mechanism was not addressed for BetA. 23 , 24 …”
mentioning
confidence: 99%
“…Early apoptotic cells are Annexin V positive and PI negative (Annexin V-FITC + /PI -), whereas late apoptotic cells are Annexin V/PI double-positive (Annexin V-FITC + /PI + ) (14,15). The total number of apoptotic cells is the sum of early and late apoptotic cells (16)(17)(18). Cells were treated with tested compounds for 48 h, harvested, washed twice with PBS and then resuspended in 500 µl of binding buffer.…”
Section: Cellular B-raf C-raf Mek1/2 Erk1/2 Caspase-3 Poly(adp-rmentioning
confidence: 99%